Combinatorial study of Fe-Co-V hard magnetic thin films - Fackler, Sean W.; Alexandrakis, Vasileios; König, Dennis; Kusne, A. Gilad; Gao, Tieren; Kramer, Matthew J.; Stasak, Drew; Lopez, Kenny; Zayac, Brad; Mehta, Apurva; Ludwig, Alfred; Takeuchi, Ichiro (Science and technology of advanced materials, 2017)
Thin film libraries of Fe-Co-V were fabricated by combinatorial sputtering to study magnetic and structural properties over wide ranges of composition and thickness by high-throughput methods: synchrotron X-ray diffraction, magnetometry, composition, and thickness were measured across the Fe-Co-V libraries. In-plane magnetic hysteresis loops were shown to have a coercive field of 23.9 kA m -1 (300 G) and magnetization of 1000 kA m -1 . The out-of-plane direction revealed enhanced coercive fields of 207 kA m -1 (2.6 kG) which was attributed to the shape anisotropy of column grains observed with electron microscopy. Angular dependence of the switching field showed that the magnetization reversal mechanism is governed by 180° domain wall pinning. In the thickness-dependent combinatorial study, co-sputtered composition spreads had a thickness ranging from 50 to 500 nm and (Fe 70 Co 30 ) 100-x V x compositions of x = 2-80. Comparison of high-throughput magneto-optical Kerr effect and traditional vibrating sample magnetometer measurements show agreement of trends in coercive fields across large composition and thickness regions.